Stakeholders’ Awareness and Acceptability of University’s Vision and Mission, and Teacher Education Program Goals and Objectives in a State Institution in Central Luzon, Philippines - Garcia, Susana; Rogayan, Danilo; Gagasa, Kenn Lesley (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The vision, mission, goals and objectives (VMGO) of any institution serve as its founding pillars in realizing its thrusts, mandates and as-pirations. This descriptive cross-sectional survey research gauged the level of awareness and acceptability of the stakeholders on the university vision and mission statement, and the goals and objectives of the teacher education programs of a state institution in Central Lu-zon, Philippines. A total of 118 stakeholders, composed of adminis-trators, faculty members, staff, alumni and students, served as the study respondents. Results showed that the stakeholders are very much aware of the university’s new vision statement and mission. They are also very much aware on the goals and objectives of the teacher education programs. Almost all stakeholders have full partic-ipation in the reformulation of the vision statement. Further, the VMGO are clear, understandable and acceptable as assessed by the university stakeholders. Massive information dissemination of the VMGO in all types of media is recommended. Stakeholders are also encouraged to take part in the realization of the university’s target outcomes and mandates.